Syngenta Enogen Feed Corn Containing an Alpha Amylase Expression Trait Improves Digestibility in Growing Calf Diets - M. A. Johnson; T. J. Spore; S. P. Montgomery; C. S. Kubick; J. S. Garzón; W. R. Hollenbeck; R. N. Wahl; C. I. Vahl; E. D. Watson; D. A. Blasi (Kansas Agricultural Experiment Station Research Reports, 2020)
Objective:To evaluate the digestibility parameters of growing cattle when fed Enogen Feed corn. Study Description:Seven cannulated Holstein steers were used to determine the effects on digestibility when fed Enogen Feed corn (Syngenta) as whole-corn or processed as dry-rolled at ad libitum intake. The Bottom Line:When Enogen Feed corn was fed in an ad libitum fashion to growing calves, dry matter and organic matter are digested to a greater extent relative to yellow corn.
Keywords: Enogen Feed corn; corn processing methods; digestibility